A Novel Efficient Address Mutation Scheme for IPv6 Networks - Yan, Shen (2017)
IP mutation is an effective moving target defense method against sniffer or hijacking attack. The mutation frequency is one of the most important parameters that influence the security of mutation method. However, higher frequency is inconsistent with data transmission that will decrease the efficiency and stability. Moreover, most of existing mutation methods have shortcomings under various conditions, such as address allocation or network architecture. In this paper, sliding window and full transparent (SWIFT) scheme for IPv6 address mutation is proposed. With the sliding window design, the SWIFT scheme can provide an address mutation with very high frequency. This scheme is transparent to both network side and user side so that the existing equipment and architecture need not to be changed. A prototype by the SWIFT scheme is designed and developed over an IPv6 network. The experiment result shows that our method can achieve high transmission efficiency with a high mutation frequency, which provides a good experience for most mutation methods.